A Retrospective Analysis of Concordance Between Clinical and Histopathologic Diagnoses and Completeness of Oral Biopsy Forms at a Tertiary Dental Hospital in Eastern Nepal - Shashi Keshwar; Neetu Jain; Toniya Raut; Vimmi Singh; Ashish Shrestha (Hindawi Limited, 2024)
Conclusions: The current study concluded a sufficient level of concordance between clinical and histopathological diagnosis. A high completion rate of biopsy forms indicated that the clinicians/operating surgeons perceive the significance of clinical information in histopathological diagnosis. We also recommend, irrespective of the type of suspected oral lesions, submitted for biopsy, a detailed clinical information is the backbone for accurate and timely reporting of the histopathological diagnosis.